ZIKV-Specific NS1 Epitopes as Serological Markers of Acute Zika Virus Infection. (4th April 2019) - Kam, Yiu-Wing; Leite, Juliana Almeida; Amrun, Siti Naqiah; Lum, Fok-Moon; Yee, Wearn-Xin; Bakar, Farhana Abu; Eng, Kai Er; Lye, David C; Leo, Yee-Sin; Chong, Chia-Yin; Freitas, Andre Ricardo Ribas; Milanez, Guilherme Paier; et al.
Abstract: Background: Zika virus (ZIKV) infections have reemerged as a global health issue due to serious clinical complications. Development of specific serological assays to detect and differentiate ZIKV from other cocirculating flaviviruses for accurate diagnosis remains a challenge. Methods: We investigated antibody responses in 51 acute ZIKV-infected adult patients from Campinas, Brazil, including 7 pregnant women who later delivered during the study. Using enzyme-linked immunosorbent assays, levels of antibody response were measured and specific epitopes identified. Results: Several antibody-binding hot spots were identified in ZIKV immunogenic antigens, including membrane, envelope (E) and nonstructural protein 1 (NS1). Interestingly, specific epitopes (2 from E and 2 from NS1) strongly recognized by ZIKV-infected patients' antibodies were identified and were not cross-recognized by dengue virus (DENV)-infected patients' antibodies. Corresponding DENV peptides were not strongly recognized by ZIKV-infected patients' antibodies. Notably, ZIKV-infected pregnant women had specific epitope recognition for ZIKV NS1 (amino acid residues 17–34), which could be a potential serological marker for early ZIKV detection. Conclusions: This study identified 6 linear ZIKV-specific epitopes for early detection of ZIKV infections. We observed differential epitope recognition between ZIKV-infected and DENV-infected patients. This information will be useful for developing diagnostic methods that differentiate between closely related flaviviruses. Abstract : This study aimed to identify specific peptides that could be used to differentiate between ZIKV and DENV infection. Six linear ZIKV-specific epitopes were identified that could be further developed into sensitive detection assays to improve diagnostic efficiency and clinical management.